Perceived Susceptibility, Severity, Benefits and Barriers in Colorectal Cancer Screening via Colonoscopy among a High Risk Population: A Comparative Study - Wongtawee, Sopana; Tantana, Tassanee; Sae-Sia, Wipa; Pruphetkaew, Nannapat; Wanitsuwan, Worrawit (Nursing Science Journal of Thailand, 2021)
Purpose: To compare the perceived susceptibility of colorectal cancer risk and severity as well as the benefits and barriers related to screening colonoscopy in individuals with hereditary CRC or an age greater than 50 years between those who underwent and did not undergo screening colonoscopy at Songklanagarind Hospital. Design: Cross-sectional comparative study. Methods: Individuals with hereditary CRC or an age greater than 50 years (N = 165) recruited from Songkhla and nearby provinces were interviewed via telephone to assess their perceived susceptibility and perceived severity of CRC as well as the benefits of and barriers to screening colonoscopy using a set of questionnaires. Data were analyzed using descriptive statistics and Fisher’s exact test and rank sum test. Main findings: There were 97 individuals in the adherence to colonoscopy screening group (59%) and 68 in the non-adherence group (41%). No significant differences regarding perceived susceptibility and perceived risk were found between the study groups. However, perceptions concerning the benefits of and barriers to colonoscopy screening were significantly different between the groups. Individuals who underwent colonoscopy perceived greater benefits (p = .002) and less barriers (p < .001), compared to their counterparts who did not undergo the screening. Conclusion and recommendations: The perceptions of the benefits of and barriers to colonoscopy screening constituted adherence factors for undergoing this procedure. Therefore, it is recommended that medical personnel provide information highlighting the benefits of colonoscopy screening and assist minimizing the existing barriers to undergoing colonoscopy among high-risk populations.